2014
DOI: 10.1155/2014/701656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extracts of Terminalia chebula on Proliferation of Keratinocytes and Fibroblasts Cells: An Alternative Approach for Wound Healing

Abstract: Terminalia chebula is one of the traditional medicines used in the treatment of many diseases. In the present work, different concentrations of various organic and aqueous extracts (solvent-free) of T. chebula were tested on fibroblast (L929) and keratinocytes cells to evaluate its biocompatible concentration by using MTT and live-dead viability/cytotoxic assay. These extracts were found to be effective in decreasing the ammonia accumulation in the media, thereby reducing its toxic effect on cells. DPPH assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Antiinflammatory and wound healing properties: Ellagitannins (geraniin, corilagin, furosin) ( Figure 1) from aqueous extracts of Phyllanthus muellerianus have been reported as active compounds with strong wound-healing properties (stimulating effects against human keratinocytes and dermal fibroblasts) [55]. Also, for pentagalloylglucose (main constituent of Paeonia suffruticosa) and for trigalloyl-glucose and gallic acid from Terminalia chebula reports have been published on potential wound healing properties [56,57]. Strong anti-hyaluronidase and anti-elastase activity was also described for lythri herba [58] Furthermore, local delivery of tannic acid prevents collagen matrix degradation by cross-linking fibrous collagen and inhibiting matrix metalloproteinase activity [59].…”
Section: Histamine Release Inhibitionmentioning
confidence: 99%
“…Antiinflammatory and wound healing properties: Ellagitannins (geraniin, corilagin, furosin) ( Figure 1) from aqueous extracts of Phyllanthus muellerianus have been reported as active compounds with strong wound-healing properties (stimulating effects against human keratinocytes and dermal fibroblasts) [55]. Also, for pentagalloylglucose (main constituent of Paeonia suffruticosa) and for trigalloyl-glucose and gallic acid from Terminalia chebula reports have been published on potential wound healing properties [56,57]. Strong anti-hyaluronidase and anti-elastase activity was also described for lythri herba [58] Furthermore, local delivery of tannic acid prevents collagen matrix degradation by cross-linking fibrous collagen and inhibiting matrix metalloproteinase activity [59].…”
Section: Histamine Release Inhibitionmentioning
confidence: 99%
“…However, the synthesis of this component of the matrix was connected to good tissue vascularization that provided oxygen and nutrients to the tissue for optimal metabolic activity of the fibroblasts and was more abundant and important for cell synthesis of the matrix components [ 2 , 37 , 38 ]. In addition to flavonoids, the compounds and phytochemicals in the B. oleracea extract included phenols, sulforanos, and anthocyanins [ 27 , 28 , 39 ], which had a positive effect on collagen type I expression and gradually influenced a reduction in the expression of collagen type III [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cellularity found in most tissues was removed from groups of mice treated with B. oleracea , which indicated an efficient repair process, and other brassicas, such as broccoli, presented sulforanos that inhibited important pathways to inflammation [ 42 ]. In inflammatory cells, fibroblasts, vascular cells that synthesized cellular mediators, and all components of the extracellular matrix had to be highlighted [ 27 ]. In this context, Angelica sinensis extract [ 42 ], diet with Centella asiatica L. [Apiaceae] [ 43 ], and Marrubium vulgare [horehound], Lamiaceae [ 44 ], rich in anthocyanins, had anti-inflammatory and antioxidant activities, which were suitable for essential skin repair.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidants are of particular interests in reducing the oxidative stress level in human organism. Some research reported that medicinal plants possess high antioxidant capacity and act at cellular level, through growth or proliferation stimulation, ROS scavenging, or lipid peroxidation [ 15 – 17 ]. Moreover, phenolic compounds, that is, phenolic acids, are known to regulate the normal human dermal fibroblast genes involved in antioxidant defense, the inflammatory response, and cell renewal [ 18 ].…”
Section: Introductionmentioning
confidence: 99%